Regionally disparate ecological responses to microplastic slowing of faecal pellets yields coherent carbon cycle response - Karin Kvale; Karin Kvale; Claire Hunt; Aidan James; Wolfgang Koeve (Frontiers in Marine Science, 2023)
Microplastic is a ubiquitous marine pollutant whose small dimensions make it biologically available to phytoplankton and zooplankton. These organisms are crucial as the basis of the marine food web and for the export of organic material in the form of faecal pellets from the surface to deeper in the water column, forming a long-term carbon sink. Previous laboratory studies have demonstrated empirically that ingestion of low density microplastics reduces the sinking rates of zooplankton faecal pellets. This study uses a complex earth system model to analyse this effect and assess its wider impacts in a changing climate. Results show that the slowing of faecal pellet sinking stimulates changes to ecosystems regionally and reduces ocean carbon uptake by about 4.4 Pg C between the years 1950-2100, 0.24% of anthropogenic emissions over this time. However, perturbation of organic particle fluxes is significant, especially in gyres, and of the order of climate change impacts over the same time period. We calculate that plastics carbon has a 3 orders of magnitude greater impact on marine ecosystems than atmospheric carbon over our centennial timescale. Large uncertainties in model parameters and simplistic model structure suggest our results should be interpreted as motivation to further investigate parameter estimation, calcification responses to pollution, and the combined effects of multiple impact mechanisms on ecosystems.